Adolescents' patterns of physical activity and psychosocial factors associated with maintenance, drop out and uptake of physical activity over twelve months - Lawler, Margaret (Trinity College (Dublin, Ireland). School of Psychology, 2016)
This thesis sought to quantitatively explore patterns of physical activity among adolescents and the psychosocial factors associated with physical activity maintenance and behaviour change over twelve months. The research is underpinned by self-determination theory (Deci & Ryan, 1985a, 2000), which provides a conceptual framework within which to investigate motivational and social-contextual processes underpinning physical activity behaviour. It has also been widely evidenced that significant others can play an important role in young people’s physical activity and as such parental and friend influences reflecting perceived support, role modelling of physical activity, acceptance from the wider peer group and negative experiences of pressure and teasing were examined. In addition, given that adolescence plays a decisive role in the development of body image, aesthetic, functional and perceptual dimensions of body image were considered alongside BMI to facilitate a greater understanding of youth physical activity. Current national estimates in line with international findings indicate that the majority of adolescents in Ireland are not sufficiently active to meet daily recommended physical activity guidelines (Woods et al., 2010). More worryingly, physical activity levels demonstrate an age-related decline, with dropout occurring earlier for girls than boys (Nader et al., 2008). Prior research has typically focused on overall levels of physical activity, thus fundamental differences pertaining to the type of physical activity underpinning total involvement has not been considered, resulting in a limited understanding of the patterns of physical activity in which young people engage. Therefore, a primary aim of this thesis was to identify profiles of adolescents’ physical activity participation using multiple indicators of physical activity (moderate-to-vigorous physical activity, non-organised physical activity (e.g. walk, jog), organised team sport, organised individual sport, and organised non-sport physical activity (e.g. dance, fitness classes). A sample of young people recruited from secondary schools completed a physical activity recall seven day diary and questionnaires tapping into motivation, competence, relatedness, autonomy, autonomy support, parental and peer support and role modelling, parental pressure, peer acceptance, teasing, body dissatisfaction and body image at two points in time, approximately one year apart. In addition, height and weight was measured objectively at each time point to obtain a measure of BMI. Latent class analysis results revealed five distinct classes among the overall sample (N = 995; Males = 386, Females = 609) at Time 1 that reflected active team sport, active individual sport, active non- organised physical activity, organised dance & fitness, and non-participation. Multiple group models indicated that the structure and prevalence of physical activity classes differed as a function of gender and age. Thus, patterns of involvement in physical activity were subsequently explored separately for male and female, and younger and older adolescents. A secondary aim of this research was to examine whether adolescents’ profiles of physical activity participation differed on a range of psychosocial and individual characteristics, given that previous studies have tended to address correlates of overall physical activity without consideration of the context or type of activity performed. The results indicated that active participation in team sport was consistently associated with more adaptive psychosocial characteristics relative to other patterns of adolescents’ physical activity. This research also addressed critical gaps in the literature by examining stability and changes in adolescents’ physical activity patterns over one year and identifying psychosocial characteristics related to physical activity dropout, uptake and maintained participation. Participants (N = 803, Males = 301, Females = 502) were followed up approximately twelve months after baseline and latent class analysis was repeated. Overall, the findings demonstrated some stability in patterns of physical activity from Time 1 to Time 2, with the most prevalent patterns of participation among each adolescent cohort replicated at follow-up. However, variations in profiles of physical activity participation also emerged at Time 2 reflecting changing patterns of youth physical activity involvement. Adolescents were then grouped longitudinally into one of four possible physical activity trajectories based on latent class membership at Time 1 and Time 2 that reflected maintained physical activity participation, dropout, continued non-participation or uptake of physical activity. The results revealed that a greater proportion of males than females, and older than younger adolescents dropped out of physical activity over twelve months. In addition, irrespective of age or gender those who engaged in team sport as compared to individual-type activities at baseline were least likely to transition into the non-participation class at follow-up. Adopting a prospective longitudinal design, mixed between-within ANOVA models were subsequently conducted to assess changes in motivational, social and body-related characteristics across adolescents’ physical activity trajectory groups from Time 1 to Time 2. The results underscore the importance of fostering self-determined motivation, autonomy, autonomy support, maternal and friend support, and functional aspects of body image for reducing dropout and promoting uptake of physical activity and continued participation during the teenage years. These psychosocial characteristics also varied in terms of relative importance for physical activity maintenance and behaviour change among male and female, and younger and older adolescents. The findings may be used to inform gender- and age-specific physical activity interventions targeting physical activity dropout across adolescence. The present research offers important advances to the physical activity literature by furthering our understanding of the different patterns of physical activity in which adolescents engage, in addition to identifying psychosocial characteristics associated with continued participation and physical activity change over twelve months.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin